2000
DOI: 10.1046/j.1365-2796.2000.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma concentrations of TGF‐β1 after hormone replacement therapy

Abstract: Abstract. Djurovic S, Os I, Hofstad AE, Abdelonoor M, Westheim A, Berg K (Ulleva Êl University Hospital and the University of Oslo, Oslo, Norway). Increased plasma concentrations of TGF-b 1 after hormone replacement therapy. J Intern Med 2000; 247: 279± 285.Objectives and design. Hormone replacement therapy (HRT) in postmenopausal women may reduce the cardiovascular risk. A dominant protective role of transforming growth factor beta (TGF-b 1 ) on coronary arteries has been proposed. Lp(a) lipoprotein may block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Furthermore, small studies have confirmed the inconsistent effect of menopausal hormones on IL-6 37,43 and have found significant reductions in TNF-␣ 40 and increases in the vasoprotective cytokine TGF-␤ in postmenopausal women treated with hormones. 44 These findings strongly suggest that the effects of menopausal hormones on CRP do not represent a generalized proinflammatory effect mediated through upstream cytokines such as IL-6 but rather are related to a secondary mechanism. 42 The finding that transdermal estradiol, unlike oral conjugated estrogen, does not elevate circulating CRP levels suggests that this secondary mechanism may be a first pass effect of CRP production in the liver after oral estrogen absorption, which is avoided by transdermal delivery.…”
Section: C-reactive Proteinmentioning
confidence: 86%
“…Furthermore, small studies have confirmed the inconsistent effect of menopausal hormones on IL-6 37,43 and have found significant reductions in TNF-␣ 40 and increases in the vasoprotective cytokine TGF-␤ in postmenopausal women treated with hormones. 44 These findings strongly suggest that the effects of menopausal hormones on CRP do not represent a generalized proinflammatory effect mediated through upstream cytokines such as IL-6 but rather are related to a secondary mechanism. 42 The finding that transdermal estradiol, unlike oral conjugated estrogen, does not elevate circulating CRP levels suggests that this secondary mechanism may be a first pass effect of CRP production in the liver after oral estrogen absorption, which is avoided by transdermal delivery.…”
Section: C-reactive Proteinmentioning
confidence: 86%
“…Among the six studies on unopposed transdermal E 2 , one reported a significant decrease compared with the untreated control group (Table 2) (31). Among the four studies on transdermal E 2 plus transdermal NETA, one found a significant decrease from baseline (57).…”
Section: Fertility and Sterility âmentioning
confidence: 95%
“…In a few studies, an initial 3-month phase of unopposed E was followed by a 3-or 9-month period of sequentially combined HT. Of these studies, the initial 3-month effect is described in the ''unopposed'' parts of the tables, whereas the end-of-study effect is given in the ''combined'' parts (31,32,36,72,84,95). The same was done for one study describing 4 weeks of unopposed transdermal E 2 followed by 2 weeks of combined HT (49).…”
Section: Trial Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Hormone replacement therapy (HRT) may have favorable effects on some cardiovascular risk factors, [3][4][5][6] but not all. 7,8 Randomized, controlled trials with conjugated equine estrogens (CEE) and accompanying gestagens have not shown any beneficial effect on cardiovascular disease or mortality in neither secondary prevention trials or during primary prevention.…”
Section: Introductionmentioning
confidence: 99%